Experimental Verification of a Digital Delay Transponder Used as an In-Ice Synthetic Aperture Radar Reference Target - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Haberberger, Niklas; Krabbe, Lena; Krieger, Gerhard; Vossiek, Martin (2023 53rd European Microwave Conference (EuMC), 2023)
Low-frequency radar systems offer great potential to support navigation systems of exploratory ice-penetrating probes for cryospheric applications. Due to the comparably small radar cross-section (RCS) of such probes, transponder-like functionalities are mandatory to realise an increased RCS for a reliable in-ice detection and localisation of these probes. To support such applications, a miniaturised monostatic digital delay transponder was developed and tested in a measurement scenario with an airborne synthetic aperture radar (SAR) sensor on an alpine glacier.<br
Keywords: Radar cross-sections; Prototypes; Tomography; Signal processing; Delays; Radar applications; Transponders; Pulse compression radar; radar cross-section (RCS); synthetic aperture radar (SAR); transponder